ChemInform Abstract: Sulfamic Acid as Energy Efficient Catalyst for Synthesis of Flurophores, 1‐H‐Spiro[isoindoline‐1, 2′‐quinazoline]‐3, 4′(3′H)‐diones. Issue 42 (September 2016) - Mane, Mansing M.; Pore, Dattaprasad M.
Abstract: The title spiro compounds are prepared by sulfamic acid‐catalyzed reaction of anthranilamide with cyclic carbonyl compounds.